Pemanfaatan Instagram Sebagai Strategi Pemasaran dalam Meningkatkan Pendapatan UMKM di Kelurahan Gunung Anyar Tambak - Cintya Sabella; Dewi Deniaty Sholihah (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
One of the pillars of economic growth is small business activities in both traditional and modern sectors through Micro, Small and Medium Enterprises (Buchari & Nurcahya, 2021). Digitalization is an important thing to understand. Problems with MSMEs in Gunung Anyar Tambak RW. 08, namely the lack of use of social media, especially Instagram as a medium for doing business. The results of the Village Development Student survey show that 70% of Micro, Small and Medium Enterprises (MSMEs) do not use Instagram as a promotional medium. Many of them are reluctant or lazy to put words together to make an interesting caption. This results in a lack of content, and a lack of consumer interest in viewing posts and visiting seller profiles. So online marketing for MSMEs in this area is not optimal. In response to these problems, socialization programs and business communication training in creating business captions/messages on Instagram are considered important instruments in building a strong foundation for the success of MSMEs. In this socialization we use lecture and discussion methods. It is hoped that this socialization and training activity will enable MSME actors in Gunung Anyar Tambak RW 08 to implement the knowledge that has been provided in the socialization on an ongoing basis, so that MSMEs through online media will progress further and get many profile visits, as well as increasing followers. The results of this service activity provide in-depth insight into how the use of social media can play a key role and have a positive impact in advancing the sustainable development of MSMEs at the village level.